Deciphering the Potential Role of Symbiotic Plant Microbiome and Amino Acid Application on Growth Performance of Chickpea Under Field Conditions - Rafique, Munazza; Ali, Abid; Naveed, Muhammad; Abbas, Tasawar; Al-Huqail, Asma A.; Siddiqui, Manzer H.; Nawaz, Ahmad; Brtnicky, Martin; Holatko, Jiri; Kintl, Antonin; Kucerik, Jiri; Mustafa, Adnan (Frontiers in Plant Science, 2022)
The unprecedented rise in the human population has increased pressure on agriculture production. To enhance the production of crops, farmers mainly rely on the use of chemical fertilizers and pesticides, which have, undoubtedly, increased the production rate but at the cost of losing sustainability of the environment in the form of genetic erosion of indigenous varieties of crops and loss of fertile land. Therefore, farming practices need to upgrade toward the use of biological agents to maintain the sustainability of agriculture and the environment. In this context, using microbial inoculants and amino acids may present a more effective, safer, economical, and sustainable alternative means of realizing higher productivity of crops. Therefore, field experiments were performed on chickpea for two succeeding years using Rhizobium and L-methionine (at three levels, i.e., 5, 10, and 15 mg L–1) separately and in combinations. The results show that the application of Rhizobium and all the three levels of L-methionine increased the growth and yield of chickpea. There was a higher response to a lower dose of L-methionine, i.e., 5 mg L–1. It has been found that maximum grain yield (39.96 and 34.5% in the first and second years, respectively) of chickpea was obtained with the combined use of Rhizobium and L-methionine (5 mg L–1). This treatment was also the most effective in enhancing nodule number (91.6 and 58.19%), leghemoglobin (161.1 and 131.3%), and protein content (45.2 and 45%) of plants in both years. Likewise, photosynthetic pigments and seed chemical composition were significantly improved by Rhizobium inoculation. However, these effects were prominent when Rhizobium inoculation was accompanied by L-methionine. In conclusion, utilizing the potential of combined use of L-methionine and microbial inoculant could be a better approach for developing sustainable agriculture production.